Signalisation of an intersection: case study / Faisal Abdul Rahman and Muhammad Shukeri Mohamad - Abdul Rahman, Faisal; Mohamad, Muhammad Shukeri (1990)
The increasing number of motor vehicles have caused certain intersections which have been previously designed to' reach their maximum capacity. Some form of measure must be taken to reduce the problems associated with it and alleviate the frustration of the road users. This study is based on the technical investigations undertaken to study the traffic flow characteristics, traffic behaviour, traffic composition, turning movements and geometric details at an identified V intersection. It involves the collection of traffic data on an hourly basis at the particular intersection chosen. A proposal on signalization at that intersection is forwarded when it was found that the existing traffic control devices are inadequate to handle the present volume at that particular intersection. Alternative proposals for improvement of the intersections include some changes of geometric layout. Long term solution suggested involve enlargement of carriageway, provision of channelization islands, slip road as well as construction of a flyover.